2020
DOI: 10.1093/pm/pnaa396
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Significantly Reduces the Use of Prescription Opioids and Improves Quality of Life in Authorized Patients: Results of a Large Prospective Study

Abstract: Objectives This article presents findings from a large prospective examination of Canadian medical cannabis patients, with a focus on the impacts of cannabis on prescription opioid use and quality of life over a 6-month period. Methods The Tilray Observational Patient Study took place at 21 medical clinics throughout Canada. This analysis includes 1,145 patients who had at least one postbaseline visit, with follow-up at 1, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 54 publications
7
37
2
1
Order By: Relevance
“…As such, our study does not support the notion that CBM/MC will reduce the use of opioids among pain patients. Some studies have found similar results to us in this respect, whereas other studies do observe a reduction in the use of opioids among users of CBM/MC (Boehnke et al, 2016;Caputi & Humphreys, 2018;Lucas et al, 2020;Nielsen, Sabioni, et al, 2017). It is also noteworthy that the rates of opioid use were relatively high, probably indicating that MC/CBM was not used as a first line of treatment.…”
Section: Discussionsupporting
confidence: 74%
“…As such, our study does not support the notion that CBM/MC will reduce the use of opioids among pain patients. Some studies have found similar results to us in this respect, whereas other studies do observe a reduction in the use of opioids among users of CBM/MC (Boehnke et al, 2016;Caputi & Humphreys, 2018;Lucas et al, 2020;Nielsen, Sabioni, et al, 2017). It is also noteworthy that the rates of opioid use were relatively high, probably indicating that MC/CBM was not used as a first line of treatment.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, there was no general opioid‐saving effect of Sativex® in all those who tried the drug. Our findings could thus be interpreted as contrary to other researchers looking into cannabis‐based medicine 22–25,32,48,49 . However, looking more closely at different patterns of Sativex® use after the initial prescription, we found that those filling only one or two prescriptions in the follow‐up year (occasional users) increased their opioids use substantially, whereas there was a decrease in those filling three or more prescriptions (frequent users).…”
Section: Discussioncontrasting
confidence: 99%
“…Recreational and medicinal cannabinoid use is expanding, including various applications to chronic pain management, and may be replacing chronic opioid and other substance use in some patients [144][145][146]. Providers should actively engage patients in shared decision-making and education regarding the perioperative implications of chronic cannabinoid use (discussed comprehensively elsewhere [147,148]), including how postoperative pain is affected.…”
Section: Perioperative Planning For the Patient With Active Substancementioning
confidence: 99%